Pengaruh Corporate Social Responsibility (CSR) terhadap Minat Beli Ulang dengan Brand Image sebagai Variabel yang Memediasi - Elisabet Yesika Sitanggang; Yunita Budi Rahayu Silintowe (Akademi Sekretari Manajemen Taruna Bakti, 2021)
The purpose of this study is to determine the effect of Corporate Social Responsibility (CSR) on repurchase intention with brand image as a mediating variable. The population of study are consumers who know the CSR program and have purchased products from PT Indofood Sukses Makmur Tbk at least more than 2 times. The method used in this research is a quantitative approach. The number of sample is 100 respondents. The data analysis used is by using the SmartPLS program. The variables of this research are Corporate Social Responsibility (CSR) as the independent variable (X), repurchase intention as the dependent variable (Y), and brand image as the mediating variable (Z). The results of this study indicate that Corporate Social Responsibility (CSR) has a positive and significant effect on brand image, brand image has a positive and significant effect on repurchase intention, Corporate Social Responsibility (CSR) has a positive and significant effect on repurchase intention and brand image mediates Corporate Social Responsibility (CSR) for repurchase intention.